Ground-based follow-up observations of TRAPPIST-1 transits in the near-infrared. Issue 2 (17th May 2019) - Burdanov, A Y; Lederer, S M; Gillon, M; Delrez, L; Ducrot, E; de Wit, J; Jehin, E; Triaud, A H M J; Lidman, C; Spitler, L; Demory, B-O; Queloz, D; et al.
Abstract: The TRAPPIST-1 planetary system is a favourable target for the atmospheric characterization of temperate earth-sized exoplanets by means of transmission spectroscopy with the forthcoming James Webb Space Telescope (JWST) . A possible obstacle to this technique could come from the photospheric heterogeneity of the host star that could affect planetary signatures in the transit transmission spectra. To constrain further this possibility, we gathered an extensive photometric data set of 25 TRAPPIST-1 transits observed in the near-IR J band (1.2 μm) with the UKIRT and the AAT, and in the NB2090 band (2.1 μm) with the VLT during the period 2015–18. In our analysis of these data, we used a special strategy aiming to ensure uniformity in our measurements and robustness in our conclusions. We reach a photometric precision of 0.003 (RMS of the residuals), and we detect no significant temporal variations of transit depths of TRAPPIST-1 b, c, e, and g over the period of 3 yr. The few transit depths measured for planets d and f hint towards some level of variability, but more measurements will be required for confirmation. Our depth measurements for planets b and c disagree with the stellar contamination spectra originating from the possible existence of bright spots of temperature 4500 K. We report updated transmission spectra for the six inner planets of the system which are globally flat for planets b and g and some structures are seen for planets c, d, e, and f.